Association of metabolic syndrome and 25‐hydroxyvitamin D with cognitive impairment among elderly Koreans. Issue 7 (22nd July 2016) - Lee, Eun Young; Lee, Su Jin; Kim, Kyoung Min; Yun, Young Mi; Song, Bo Mi; Kim, Jong Eun; Kim, Hyeon Chang; Rhee, Yumie; Youm, Yoosik; Kim, Chang Oh
Abstract: Aim: Metabolic syndrome and vitamin D deficiency are prevalent in older adults, and are considered risk factors for cognitive impairment. We investigated the combined effects of MetS and serum 25‐hydroxyvitamin D (25[OH]D) levels on cognitive function in older adults. Methods: We studied 2940 participants aged ≥65 years from the Korean Urban Rural Elderly cohort study. Metabolic syndrome was defined according to the updated Adult Treatment Panel III criteria. Serum 25(OH)D levels were categorized into four groups: <25, 25–49, 50–74 and ≥75 nmol/L. Cognitive function was assessed using the Mini‐Mental State Examination. Results: Participants with cognitive impairment had higher metabolic syndrome prevalence and lower serum 25(OH)D levels than those without cognitive impairment. In univariate analysis, both metabolic syndrome and low 25(OH)D levels were associated with cognitive impairment. These associations remained unchanged after adjusting for potential confounders including age, sex, season and education. In addition, participants with metabolic syndrome and low 25(OH)D had significantly increased odds for cognitive impairment (odds ratio 3.06, 95% CI 1.61–5.80) when compared with those with no metabolic syndrome and high 25(OH)D. Conclusions: Metabolic syndrome was associated with cognitive impairment, and this risk was synergistically increased when metabolic syndrome was combined with low 25(OH)D. A focus on individuals with metabolic syndrome and low 25(OH)D might be helpful to identify older adults who are at risk of cognitive impairment.Geriatr Gerontol Int 2017; 17: 1069–1075 .